Analysis Influence Various Types of Promotions Sale To Behavior Purchase Consumers : Case Study at Niaga Supermarket , Lombok - suleman, Dede; Sabil, Sabil; Ati Haryati, Raden; Wianti, Wiwin; Sofyanty, Devy (Dinasti Publisher, 2024)
Research This aim For investigate impact various type promotion sale to behavior purchase consumers at Niaga Supermarket , Lombok. Through analysis of survey data involving sample consumer from the supermarket , research This disclose relevant findings . _ Research result show that promotion